The Level of Practicing Educational Competencies among Students in Practical Education from their Perspectives in the Light of Some Variables (A field study for fourth year students- a teacher of class- at the Faculty of Education in Tartous University) - Jnad, Rawah; Sultan, Manal; Mohammad, Siba (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This research aimed to measure the degree of the practicing of educational competencies by the students of the fourth year - the teacher of the first cycle of basic education- in the course of practical education, and to investigate the impact of sex, and secondary certificate on this degree. To achieve that, the researcher used the descriptive approach, and prepared a questionnaire for the educational competencies containing (42) sections divided into three axes (planning, implementation and evaluation), as it was ascertained validity and reliability, and distributed to a sample of (102) students of the fourth year (the teacher of the first cycle of basic education) at the faculty of education in Tartuos university. The results showed that the research sample practice the educational competencies in a high degree, and that male students engage in the educational competencies equally exercised by the female students, and the results also showed the absence of statistically significant differences in practices of educational competencies among students due to the variable of Secondary Certificate. The researcher suggested the designing and implementing training programs for the development of evaluation adequacy among students in the faculties of education.